An extended grey relational analysis method : a case study on ranking overall energy sustainability performances of OECD countries - Altıntaş, Koray (My University, 2021)
İnsanoğlu kaynakların tükenmesi, sosyal eşitsizlikler, enerji kaynaklarına ulaşımda sıkıntılar, ve çevresel kaygılar gibi global problemlerin olduğu bir çağda yaşamaktadır. Bu durum araştırmacıların sürdürülebilirlik ve birbiriyle çelişen ihtiyaçlarda dengenin nasıl sağlanabileceğine dair çalışmalar yapmasını da beraberinde getirmiştir. Ancak sürdürülebilirlik konseptinin kompleks ve çok boyutlu olması nedeni ile bu araştırmacılar için zor bir görev olmuştur. Dolayısıyla, sürdürülebilirliğin değişik alanlarında yapılan ilerlemelerin ölçülmesi büyük önem arz etmektedir. Uygulamaya bağlı olarak, çok kriterli karar verme yöntemleri alternatifler arasında karşılaştırma yapmak ve en ideal alternatifi bulmak gibi alanlarda oldukça yaygın bir şekile kullanılmaktadır. Bu konu özellikle enerji sürdürülebilirliği açısından ülkelerin birbiri ile karşılaştırılması noktasında önemlidir. Ülkeleri, önceden belirlenmiş değişik kriterleri göz önünde bulundurarak birbiri ile karşılaştırabilen indeksler hem araştırmacılara hem de politika yapıcılara yararlı araçlar olarak karşımıza çıkmaktadır. Bu noktada, bulanık mantık ortamında analitik hiyerarşi prosesi modeli ile entegre edilmiş gri ilişkisel analiz yönteminin revize edilmiş ve genişletilmiş versiyonunu kullanarak 35 OECD ülkesinin enerji sürdürülebilirliğini inceleyen bir indeks çalışması ortaya koyduk. Bu çalışmanın amacı hali hazırda mevcut olan gri ilişkisel analiz normalizasyon prosedürüne eklemeler ve revizyonlar yaparak değişik ülkelerin enerji sürdürülebilirlik performanslarını ölçebilecek bir yöntem sunmaktır. Önerilen yöntem yapısı gereği sürdürülebilirliğin değişik alanlarında da uygulanabilir.

We are living in an age where major global issues like depletion of sources, social inequity, lack of energy accessibility and environmental concerns began to draw more and more attention. This have triggered numerous researches on sustainability and how to achieve it by focusing on solutions to balance the fine line between competing needs. However, it has been a tough task due to the complex and multidimensional nature of sustainability. Therefore, it is vital to determine methods to measure the progress of human action towards sustainable development in different areas of sustainability. Depending on the application, multi-criteria decision-making methods have been widely used for making comparisons between alternatives and finding the optimum one among them. This has been an interesting research topic for comparing the performances of different countries from energy sustainability point of view. Developing an index that allows to compare countries depending on their performances for various criteria can be a useful tool for researchers and policy makers. We have proposed an extended and revised version of the grey relational analysis method, which is integrated with the fuzzy analytic hierarchy process to develop a new composite index for comparing the overall energy sustainability performances of 35 OECD member countries. The aim of this dissertation is to introduce new extensions to the current grey relational analysis normalization procedure to capture overall energy sustainability performances of different countries. Proposed method can be used in different applications of sustainability due to its flexible nature since it provides benefits from goal-oriented extensions to capture different aspects of sustainability.
Keywords: bulanık mantık ortamında analitik hiyerarşi prosesi; composite index; çok kriterli karar verme teknikleri; Enerji sürdürülebilirliği; Engineering; extended grey relational analysis; fuzzy analytic hierarchy process; Güç kaynakları; indeks; izleme aracı Overall energy sustainability; Management; monitoring tool; multi-criteria decision-making; Mühendislik; OECD countries; OECD member countries; OECD ülkeleri; Power resources; Sustainability; Sürdürülebilirlik; Yönetim